Sistem Pengendalian Internal Sanksi Adat Pada Tradisi Mutranin - Dewi, Ni Kadek Sanchi Krisna; Yasa, I Nyoman Putra (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
Credit is generally carried out by formal financial institutions. However, in Nagasepaha Village, credit is called mutranin. Mutranin is religious in nature because it is carried out in an informal socio-religious organization, namely Nagasepaha Traditional Village. Because it is religious in nature, krama must comply with the rules of the traditional village called awig-awig, both written and unwritten. The purpose of this study is to describe how the implementation of customary sanctions as an internal control system in the mutranin tradition by Nagasepaha Traditional Village. The benefits of this research are as reference material and study for further research and as input for Nagasepaha Traditional Village. This research uses descriptive qualitative method. The resource persons of this study were the kelian, treasurer, village officials and the Nagasepaha Traditional Village manners. The result of this research is that customary sanctions as an internal control system in the mutranin tradition have fulfilled the SPI elements according to IAPI. The customary sanctions given consist of panicle sanctions, sanctions announced in sangkepan and kasepekang sanctions which can raise awareness of village manners in fulfilling their obligations.Â Â Â